EVALUASI STRUKTUR GEDUNG FAKULTAS HUKUM UNIVERSITAS ISLAM INDONESIA YOGYAKARTA BERDASARKAN PERCEPATAN GEMPA YANG DIHITUNG SECARA PROBABILISTIK - Wisnu Erlangga; Lalu Makrup; Malik Musthofa; Suharyatmo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Earthquake shocks generally cause the biggest shocks in building structures. Earthquake waves, generated by an earthquake event, are the main cause of this shaking. A new building of the Faculty of Law, Islamic University of Indonesia, was selected for this research to evaluate the effect of earthquake shaking on the structural response. A developed time history-based artificial earthquake ground motion was used in the structural analysis. Furthermore, the time history was developed based on spectral matching with target spectra derived from a probabilistic seismic hazard analysis. This analysis results in the building structure's seismic response, which is then evaluated based on the parameters set by the earthquake standards/regulations for buildings. This building is relatively safe against design earthquake shocks based on the results.